Implementasi Manajemen Sumber Daya Manusia dalam Kegiatan Rekrutmen Petugas Ibadah Haji Kantor Kementerian Agama Kabupaten Kendal Tahun 2023 - Siti Fatimah; Ahmad Anas (Dinasti Review, 2024)
Recruitment of Hajj officers is the first way to find a competent Hajj officer or guide. In looking for quality human resources, there needs to be a strict selection process in order to find Hajj officers who are truly competent and capable in this field. This research uses a descriptive qualitative method, by describing the results of interviews and observations. The aim of this research is to find out thoroughly how the Hajj Officer Recruitment process is and the form of human resource management implemented. The research results show that the form of implementation of human resource management is said to be successful because there is preparation and planning of human resources in accordance with the management functions implemented in the Hajj Officer recruitment activities referring to Planning, Organizing, Actuating, Controlling. The form of implementing human resource management to obtain qualified and competent Hajj officers is through training or equipping activities for Hajj officers carried out at the provincial level with the aim of improving the quality of Hajj officers, improving conceptual characteristics and leadership qualities.